Frequency and impact of summertime stratospheric intrusions over Maryland during DISCOVER‐AQ (2011): New evidence from NASA's GEOS‐5 simulations. Issue 7 (14th April 2016) - Ott, Lesley E.; Duncan, Bryan N.; Thompson, Anne M.; Diskin, Glenn; Fasnacht, Zachary; Langford, Andrew O.; Lin, Meiyun; Molod, Andrea M.; Nielsen, J. Eric; Pusede, Sally E.; Wargan, Krzysztof; Weinheimer, Andrew J.; et al.
Abstract: Aircraft observations and ozonesonde profiles collected on 14 and 27 July 2011, during the Maryland month‐long Deriving Information on Surface conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER‐AQ) campaign, indicate the presence of stratospheric air just above the planetary boundary layer (PBL). This raises the question of whether summer stratospheric intrusions (SIs) elevate surface ozone levels and to what degree they influence background ozone levels and contribute to ozone production. We used idealized stratospheric air tracers, along with observations, to determine the frequency and extent of SIs in Maryland during July 2011. On 4 of 14 flight days, SIs were detected in layers that the aircraft encountered above the PBL from the coincidence of enhanced ozone, moderate CO, and low moisture. Satellite observations of lower tropospheric humidity confirmed the occurrence of synoptic‐scale influence of SIs as do simulations with the GEOS‐5 atmospheric general circulation model. The evolution of GEOS‐5 stratospheric air tracers agrees with the timing and location of observed stratospheric influence and indicates that more than 50% of air in SI layers above the PBL had resided in the stratosphere within the previous 14 days. Despite having a strong influence in the lower free troposphere, these events did not significantly affect surface ozone, which remained low on intrusion days. The model indicates similar frequencies of stratospheric influence during all summers from 2009 to 2013. GEOS‐5 results suggest that over Maryland, the strong inversion capping the summer PBL limits downward mixing of stratospheric air during much of the day, helping to preserve low surface ozone associated with frontal passages that precede SIs. Key Points: Eastern U.S. stratospheric intrusions can strongly influence composition of lower free troposphere High‐resolution global models reproduce temporal evolution and dynamical structure of these events Summertime stratospheric intrusions have implications for air quality